2018
DOI: 10.1162/jocn_a_01198
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Selective Alpha Oscillations Reveal Moment-by-Moment Trade-offs between Working Memory and Attention

Abstract: Current theories assume a functional role for covert attention in the maintenance of spatial information in working memory. Consistent with this view, both the locus of attention and positions stored in working memory can be decoded based on the topography of oscillatory alpha-band (8–12 Hz) activity on the scalp. Thus far, however, alpha modulation has been studied in isolation for covert attention and working memory tasks. Here, we applied an inverted spatial encoding model in combination with EEG to study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 46 publications
13
62
0
Order By: Relevance
“…It is also possible that strategies differed across participants. In contrast, and in line with previous studies of spatial attention, repeating the target location was associated with reliable spatial tuning to the target location in advance of stimulus presentation (Fig. 2A; top row).…”
Section: Indirect Preparatory Distractor Suppressionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is also possible that strategies differed across participants. In contrast, and in line with previous studies of spatial attention, repeating the target location was associated with reliable spatial tuning to the target location in advance of stimulus presentation (Fig. 2A; top row).…”
Section: Indirect Preparatory Distractor Suppressionsupporting
confidence: 91%
“…That is, while the evidence for alpha-band oscillatory activity in direct, top-down inhibition is ambiguous, as discussed above, many studies have now shown that the focus of attention can be decoded from the pattern of alpha-band EEG activity even before stimulus presentation. [90][91][92] These and other findings support the notion that one important role for alpha oscillations may be to enhance signal-to-noise ratio within task-relevant regions by suppressing noise. 20 Suppression of neuronal activity within task-relevant sensory regions through alpha-band oscillations could, when at an intermediate level, suppress activity of neurons with low activity to begin with, but not of neurons with high activity to begin with (i.e., those representing the attended, task-relevant information), thereby increasing the signal-tonoise ratio.…”
Section: Inhibition In Task-relevant Networksupporting
confidence: 67%
See 1 more Smart Citation
“…Based on previous research (Foster et al, 2017;Samaha et al, 2016;van Moorselaar et al, 2018), we expected any effects to be especially present in the alphaband. An analysis collapsed across conditions and repetitions across a range of frequencies confirmed that sustained reconstruction of both the target and the distractor location was especially pronounced within the alpha-band (8 -12 Hz; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, we collapsed across channels that were equidistant from the center and used linear regression to calculate the slope of the CTF, where a positive slope indicates greater location selectivity (relative to the other locations), a flat slope no location specificity, and a negative slope reduced location selectivity (relative to the other locations). Previous work using IEMs has demonstrated that the reconstruction of spatially selective CTFs during preparatory spatial attention is largely specific to power in the alpha band (Foster et al, 2017;Samaha et al, 2016;van Moorselaar et al, 2018). To isolate frequency-specific activity, we band-pass filtered the data using a fifth-order butterworth bandpass filter within MNE.…”
Section: Methodsmentioning
confidence: 99%